2016
DOI: 10.3382/ps/pev343
|View full text |Cite
|
Sign up to set email alerts
|

Early experiences matter: a review of the effects of prenatal environment on offspring characteristics in poultry

Abstract: Early life experiences can be important in determining offspring phenotypes and may influence interaction with the environment and hence health, welfare, and productivity. The prenatal environment of poultry can be divided into the pre-lay environment and the egg storage/incubation environment, both of which can affect offspring outcomes. The ability to separate maternal and egg/incubation effects makes birds well suited to this type of research. There are many factors, including feeding and nutrition, environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 106 publications
(145 reference statements)
1
44
0
1
Order By: Relevance
“…Its effects are highly dependent on the intensity, timing of exposure, and type of stressor experienced by the mother (4)(5)(6). More specifically, impacts on offspring behavior are evident across taxa [avian (7); mammals (1,8); reptiles (9)], and at the neurological scale, maternal stress has been linked to structural and functional changes in the limbic system and prefrontal cortex of rats (1), and to changes in gene expression in the hypothalamus of chickens (10). These brain areas are involved in the mediation of fear and anxiety, social and cognitive processes, and working memory of mammals and birds (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Its effects are highly dependent on the intensity, timing of exposure, and type of stressor experienced by the mother (4)(5)(6). More specifically, impacts on offspring behavior are evident across taxa [avian (7); mammals (1,8); reptiles (9)], and at the neurological scale, maternal stress has been linked to structural and functional changes in the limbic system and prefrontal cortex of rats (1), and to changes in gene expression in the hypothalamus of chickens (10). These brain areas are involved in the mediation of fear and anxiety, social and cognitive processes, and working memory of mammals and birds (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Hens primarily determine the development of offspring embryos and the postnatal growth [87]. At the same time, the weight of a fertilized chicken egg affects the hatch and growth of their offspring, and this maternal environment can influence the growth characteristics of their progeny lastingly [88]. Although offspring of plasma-treated parents fail to inherit excellent growth properties, non-thermal DBD plasma direct-treated generation suggests a potentially viable and valuable strategy to improve the chicken growth rate in the poultry industry.…”
Section: Plasma Application In Chicken Growthmentioning
confidence: 99%
“…The effects of maternal stress in the offspring of birds and mammals are highly dependent on the intensity, timing of exposure and type of stressor experienced by the mother (5–7). Maternal stress can impact offspring’s physiology, behaviour and cognition (6,8) through structural and functional changes in brain areas involved in the mediation of fear and anxiety (9), as well as through changes in gene expression (10). We have previously shown that chicks from a commercial line of layer breeders that were subjected to daily sessions of psychological stressors during egg production showed a decreased occurrence of anxiety-like behaviour (measured in the total number of distress calls expressed during social isolation) compared to a control group (11).…”
Section: Introductionmentioning
confidence: 99%